Investigating the influence of ecological dynamics on player density metrics in junior Australian football - Sutherland, T.; Reid, M.; Lay, B.; Kirkham, T.; Peeling, P. (Journal of Sports Sciences, 2025)
Player density can largely influence skill development in junior sport. Accordingly, we aimed to evaluate how player density metrics change in the context of the ecological dynamics framework in community-level junior Australian Football (AF). Game footage (n = 68 games) from under (U)9-U14 were analysed for player density metrics, sub-categorised as: ball-up metrics (total number of ball-ups, repeat ball-ups, clearances, and the number of players at a ball-up [within 3 m]), pressure (i.e. physical, closing, chasing, none, set), and opposition count (number of opposition players within 3 m of a disposal). Linear regression models analysed each player density metric, accounting for variables such as age, sex, relative area per player (RAPP), number of players in the game, and weather. Girls had more total and repeat ball-ups per game than boys (both p < 0.001). Younger age-groups experienced more players around ball-ups (p < 0.05). Total ball-ups were reduced with increased RAPP (p = 0.006). Physical pressure was not influenced by any variable, but occurred most frequently across all cohorts. This study provides novel exploration of player density metrics in junior AF, highlighting increased density experienced by younger age-groups and girls at ball-ups. These findings also suggest RAPP manipulation as a practical method of reducing ball-up frequency in junior AF.